Task-Based Learning : An Approach for Thai Reading and Writing Teaching Development - Phiwhlueng, Atthaphong; Pawaradhmmo, Phra Boworn; Thammabut, Bancha; Athan, Manmit (Journal of Graduate MCU KhonKaen Campus, 2022)
This article of objective for presenting Reading and Writing Teaching of Task-Based Learning so a development of Thai reading and writing teaching whit task-based learning, focus on making the learner weak in pronunciation according to the principle of correct Thai tonal conjugation, able to write Thai words correctly according to the Thai tone and meets the meaning that needs to be communicated because reading and writing are essential to communication. Except task-based learning for Thai reading and writing teaching is applying knowledge from the three sciences: linguistics, teaching method and Thai language to integrate learning management.